Indigenous Biopreparations and Biocontrol Agents for Growth and Disease Management in Black Pepper Nursery - Rini, C. R.; Ajith, P. M. (International Journal of Economic Plants, 2023)
The present study was carried out at Agricultural Research Station, Thiruvalla, Kerala, India during December, 2020–July, 2021 to evaluate the efficacy of native biocontrol agents and fermented organic preparations viz; fish-jaggery extract, egg-lemon juice extract and jeevamrutha on growth enhancement and suppression of Phytophthora infection in black pepper nursery. The plants were challenge inoculated with Phytophthora capsici at the collar region. The plant growth parameters were recorded before and one month after treatment application. Results showed that a considerable increase in plant height (49.30%) and number of leaves (57.89%) with the application of bacterial antagonists A1 and S2 respectively. Application of fish-jaggery extract increased the shoot girth by 29.6%. Soil application of Trichoderma combined with spraying of bacterial antagonists A1 and S2 also increased the shoot girth considerably. Application of jeevamrutha increased the total leaf area by 49.98% and chlorophyll contents viz. chlorophyll a, chlorophyll b and total chlorophyll was also maximum with this application. Phytophthora infection at collar region was not observed in plants treated with potassium phosphonate and fish-jaggery extract. Application of egg-lemon juice extract, jeevamrutha and bioagents also recorded less infection on collar region. The study indicated the efficacy of fermented organic fertilizers and bioagents in improving plant growth and also in reducing pathogen infection at nursery stage. Hence a combination of native antagonistic microflora and indigenous biopreparations could be effectively utilized in commercial production of healthy planting materials in black pepper nurseries.